Cost-Efficient Privacy-Preserving Authentication and Key Management Scheme for Internet of Vehicle Ecosystem - Tahir Ali Shah; Fahad Algarni; Insaf Ullah; Ako Muhammad Abdullah; Fazal Noor; Muhammad Asghar Khan (Complexity)
Internet of vehicles (IoV) is an emerging area of advanced transportation systems, in which the functionality of traditional vehicular ad hoc networks (VANET) combined with the Internet of things (IoT). This technology allows vehicle users and drivers to interact in real time from anywhere and anytime. However, until recently, the major two problems that authentication and key management methods may solve are security and privacy. In this study, we offer a privacy-preserving authentication and key management scheme for the IoV environment that is computationally and communication cost-effective. We conducted a thorough security analysis, demonstrating that the proposed scheme is resistant to a variety of cryptographic attacks. We have included a cost analysis that indicates the proposed scheme is more efficient than IoV’s current privacy-preserving authentication and key management schemes.